Legal Enforcement Efforts On Traffic Violations Made By Students Under The Age In Surabaya City - Ebit Rudianto; Vivin Indrianita; Mohammad Roesli (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2021)
Law enforcement in the State is carried out in a preventive and repressive manner. Preventive law enforcement is in place to prevent violations of the law by citizens and this task is generally assigned to the executive bodies and the police. Repressive law enforcement at the operational level (its implementation) is supported and through various institutions that are organizationally separate from one another, but remain within the framework of law enforcement, starting from: the Police, the Attorney General's Office, the Courts, to Correctional Institutions. There are many problems related to law violations, ranging from minor to severe. Minor offenses that often occur in traffic problems, such as not wearing a helmet, running a red light, not having a SIM or STNK, not turning on the lights during the day, and hitchhiking are considered cultured among the community and school students. Traffic violations like that are considered to have become a habit for road users, so that every time an orderly operation of traffic is carried out on the highway by the authorities, not a few cases of traffic violations are caught and often because these violations often lead to traffic accidents. cross. Driving a vehicle inadvertently and exceeding the maximum speed seems to be an immature behavior. However, most drivers are aware of the dangers faced when driving a vehicle over this maximum speed. However, in reality, there are not a few drivers who do this, especially school students, so that many traffic violations cause traffic accidents.